Simply Artificial Intelligence - Quigley, Claire (New York, NY : DK Publishing, 2023)
"Explaining each individual aspect of AI more clearly than ever before, the book outlines the key building-blocks and technological milestones in its history, profiles its most important practical applications--both current and predicted--and explores the numerous ethical debates around AI, and its increasing influence on culture and society"--
History of artificial intelligence -- Classical artificial intelligence -- Statistical artificial intelligence -- Using artificial intelligence -- Philosophy of artificial intelligence -- Living with artificial intelligence.
Includes index.
Keywords: Artificial intelligence -- Popular works; Artificial intelligence; Popular works